Growing transformational future livestock sector professionals - Emerging impacts of the ILRI CapDev grand challenge - Ekaya, Wellington N. (International Livestock Research Institute, 2021)
In 2019, the International Livestock Research Institute (ILRI) launched a new initiative, the ‘CapDev Grand Challenge’, an approach to grow cohorts of transformational future livestock sector professionals. The target group is graduate students and researchers from national organisations in LMICs where ILRI works. Annually ILRI hosts about 100 PhD and MSc students embedded within its research programs and co-supervised by professors from degree-awarding universities where the students are registered. Designed to complement graduate research and technical/scientific training, the Challenge process aims at boosting soft skills and systems thinking capability.